2018
DOI: 10.1007/s00394-018-1654-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fructose intake does not induce liver steatosis and inflammation in female Sprague–Dawley rats, but causes hypertriglyceridemia related to decreased VLDL receptor expression

Abstract: Chronic liquid simple sugar supplementation, as the sole risk factor, is not enough for female rats to develop NASH and increased liver gluconeogenesis. Nevertheless, under isocaloric conditions, only fructose induced hypertriglyceridemia, thus confirming that also the type of nutrient matters in the development of metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 55 publications
6
26
0
Order By: Relevance
“…Liver, vWAT, and body weight, solid food, and liquid intake, as well as energy consumption of female Sprague‐Dawley rats supplemented chronically with liquid fructose and glucose, have been reported previously . In brief, both sugar‐supplemented rats increased their total energy intake by 55%.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Liver, vWAT, and body weight, solid food, and liquid intake, as well as energy consumption of female Sprague‐Dawley rats supplemented chronically with liquid fructose and glucose, have been reported previously . In brief, both sugar‐supplemented rats increased their total energy intake by 55%.…”
Section: Resultssupporting
confidence: 64%
“…Considering that one rat month is approximately equivalent to three human years, this supplementation period is roughly equivalent to 15–20 years of human life. Using this experimental model, we have previously shown that, despite an increase in daily calorie intake of more than 50% with respect to control animals, liver homeostatic mechanisms reverts the liver fat deposition previously observed in fructose‐supplemented rats over shorter periods of time, probably by a specific activation of the inositol requiring enzyme 1 branch of the unfolded protein response . However, rats supplemented with fructose for 7 months clearly showed extra‐hepatic impaired insulin signaling and glucose intolerance, two metabolic alterations already detected in rats supplemented with fructose for 2 months .…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…; Alwahsh and Gebhardt ), it was also shown that chronic supplementation with fructose (10%, w/v) for 7 months did not induce hepatic steatosis and inflammation in female Sprague–Dawley rats (Sangüesa et al. ).…”
Section: Discussionmentioning
confidence: 94%